Menopausal symptoms and quality of life in Turkish women in the climacteric period. (December 2014) - Ceylan, B.; Özerdoğan, N.
Abstract Objectives The purpose of this study is to determine the frequency of menopausal symptoms in Turkish women and the impact of these symptoms and related factors on the quality of life. Methods The sample in this cross-sectional study consisted of 1030 women, aged 40–59 years. The researcher collected the data at the women's homes via the face-to-face interview method using the Menopause-Specific Quality of Life (MENQOL) questionnaire and a questionnaire developed and drawn up in line with the literature. Results The mean age (± standard deviation) of the women participating in the study was 48.58 ± 5.61 years and their mean menopausal age was 46.4 ± 4.4 years. While the most frequently experienced menopausal symptoms in the study were feeling tired and worn out (79.2%), aches in the muscles and joints (79.1%) and low backache (77.8%), the least experienced symptom was an increase in facial hair (28.3%). Significant differences were found between the subdomain mean scores on the MENQOL according to menopausal periods (p = 0.000). Significant differences were detected in all subdomain mean scores of the MENQOL questionnaire according to age groups, perception of income, education, parity and body mass index (p < 0.05). Conclusion In women in the climacteric period, the time that quality of life is the most affected among all the menopausal periods is the postmenopausal period. Women in menopause should not be forgotten; health-care services addressing the health needs of women should not be restricted only to the period of fertility but continued with the same sensitivity throughout the life cycle.